Cardiovascular Benefits of Native GLP-1 and its Metabolites: An Indicator for GLP-1-Therapy Strategies - Li, Junfeng; Zheng, Juan; Wang, Susanne; Lau, Harry K.; Fathi, Ali; Wang, Qinghua (Frontiers in Physiology, 2017)
Cardiovascular disease is a common co-morbidity and leading cause of death in patients with type 2 diabetes mellitus (T2DM). Glucagon-like peptide 1 (GLP-1) is a peptide hormone produced by intestinal L cells in response to feeding. Native GLP-1 (7-36) amide is rapidly degraded by diaminopeptidyl peptidase-4 (DPP4) to GLP-1 (9-36) amide, making 9-36a the major circulating form. While it is 7-36a, and not its metabolites, which exerts trophic effects on islet β-cells, recent studies suggest that both 7-36a and its metabolites have direct cardiovascular effects, including preserving cardiomyocyte viability, ameliorating cardiac function and vasodilation. In particular, the difference in cardiovascular effects between 7-36a and 9-36a is attracting attention. Growing evidence has strengthened the presumption that their cardiovascular effects are overlapping, but distinct and complementary to each other; 7-36a exerts cardiovascular effects in a GLP-1 receptor (GLP-1R) dependent pathway, whereas 9-36a does so in a GLP-1R independent pathway. GLP-1 therapies have been developed using two main strategies: DPP4-resistant GLP-1 analogues/GLP-1R agonists and DPP4 inhibitors, which both aim to prolong the life-time of circulating 7-36a. One prominent concern that should be addressed is that the cardiovascular benefits of 9-36a are lacking in these strategies. This review attempts to differentiate the cardiovascular effects between 7-36a and 9-36a in order to provide new insights into GLP-1 physiology, and facilitate our efforts to develop a superior GLP-1-therapy strategy for T2DM and cardiovascular diseases.